Measurement of the Ds+ - Ds- production asymmetry in 7 TeV pp collisions - Aaij, Roel; Adametz, Aleksandra; Bachmann, Sebastian; Bien, Alexander; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Jäger, Andreas; Kreplin, Katharina; Krocker, Georg Alexander; Linn, Christian; et al. (Physics letters, 2012)
Heavy quark production in 7 TeV centre-of-mass energy pp collisions at the LHC is not necessarily flavour symmetric. The production asymmetry, AP, between Ds+ and Ds− mesons is studied using the ϕπ± decay mode in a data sample of 1.0 fb−1 collected with the LHCb detector. The difference between π+ and π− detection efficiencies is determined using the ratios of fully reconstructed to partially reconstructed D⁎± decays. The overall production asymmetry in the Ds± rapidity region 2.0 to 4.5 with transverse momentum larger than 2 GeV is measured to be AP=(−0.33±0.22±0.10)%. This result can constrain models of heavy flavour production.